Pain in the neck and shoulder joint in a rheumatologist's practice - Yuri Aleksandrovich Olyunin (Современная ревматология, 2012)
Diseases accompanied by pain in the neck and shoulder joint are rather numerous, frequently result in permanent functional failure, and are encountered in a considerable number of patients followed up by rheumatologists, neurologists, orthopedics, and therapists. The frequency of these impairments may vary from 7 to 47% according to the characteristics of the study population and used definition. The list of nosological entities to be excluded in the differential diagnosis includes diseases caused by lesions in the cervical spinal area, its muscles, ligaments, and tendons, neurological changes, systemic inflammatory diseases, myofascial pain syndrome, as well as diseases that can induce referred pain in the neck and shoulder joint (pneumonia, coronary heart disease, gastroduodenal ulcer disease). To follow a sparing regimen plays a large role in the treatment of soft tissue diseases in the shoulder joint. The use of analgesics, primarily nonsteroidal anti-inflammatory drugs (NSAIDs), such as nimesulide (nayz), is an important component of therapy. The drug has been successfully used for back pain, osteoarthrosis, and extraarticular soft tissue diseases. The local administration of glucocorticoids is worth consideration if a reduced load on the affected area and the use of NSAIDs produce no desirable effect.